1994
DOI: 10.1210/endo.134.6.8194485
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor increases the rate of lipolysis in primary cultures of adipocytes without altering levels of hormone-sensitive lipase.

Abstract: To investigate the effects of cytokines on adipocyte lipolysis, a macrophage cell line (RAW 264.7) was treated with Escherichia coli lipopolysaccharide (1 microgram/ml) for 18 h to induce cytokine release. Conditioned medium (5%, vol/vol) from these cells was added to rat epididymal adipocytes isolated and incubated under sterile conditions. After incubation, the adipocytes were washed, and the rate of lipolysis (glycerol release) was determined after a further 1-h incubation. The conditioned medium caused an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(27 citation statements)
references
References 33 publications
2
24
0
Order By: Relevance
“…An early study showed that the conditioned medium of LPS-stimulated macrophages increased lipolysis in adipocytes, an effect thought to result from elevated TNF-␣ secretion by LPS, not from LPS itself, although this conditioned medium contained at least 0.05 g/ml LPS (19). We observed that when original LPS residues in the conditioned medium of LPS-stimulated adipocytes were neutralized by the anti-endotoxin BNEP, the conditioned medium could not elevate lipolysis.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…An early study showed that the conditioned medium of LPS-stimulated macrophages increased lipolysis in adipocytes, an effect thought to result from elevated TNF-␣ secretion by LPS, not from LPS itself, although this conditioned medium contained at least 0.05 g/ml LPS (19). We observed that when original LPS residues in the conditioned medium of LPS-stimulated adipocytes were neutralized by the anti-endotoxin BNEP, the conditioned medium could not elevate lipolysis.…”
Section: Discussionmentioning
confidence: 64%
“…Adipocytokine or NFB Activation Is Not Involved in LPS-stimulated Lipolysis-An early study showed that the conditioned medium of LPS-stimulated macrophages increased lipolysis, but this effect may have resulted from increased TNF-␣ secretion from LPS-stimulated microphages (19). We therefore investigated whether the cytokine secretion from adipocytes accounts for LPS-stimulated lipolysis.…”
Section: Lps-stimulated Lipolysis Depends On Its Lipid a Moiety And Imentioning
confidence: 95%
See 1 more Smart Citation
“…Although a previous report indicates that TNF-␣ down-regulates ATGL and HSL mRNA (53), we find that TNF-␣ does not alter their protein levels in 3T3-L1 adipocytes. Parallel observations were obtained from primary rat adipocytes treated with TNF-␣ (39,54). Most importantly, we demonstrate that HSL and ATGL are both required for the lipolytic response to TNF-␣.…”
Section: Discussionmentioning
confidence: 79%
“…Statistical analysis was determined by Student's t test or one-way analysis of variance. (39,41,45,46). To examine the modulation of individual players in the lipolytic proteome, we treated fully differentiated 3T3-L1 adipocytes with TNF-␣ for various periods of time.…”
Section: Methodsmentioning
confidence: 99%